Cellular functions of the ClpP protease impacting bacterial virulence - Aljghami, Mazen E.; Barghash, Marim M.; Majaesic, Emily; Bhandari, Vaibhav; Houry, Walid A. (Frontiers in Molecular Biosciences, 2022)
Proteostasis mechanisms significantly contribute to the sculpting of the proteomes of all living organisms. ClpXP is a central AAA+ chaperone-protease complex present in both prokaryotes and eukaryotes that facilitates the unfolding and subsequent degradation of target substrates. ClpX is a hexameric unfoldase ATPase, while ClpP is a tetradecameric serine protease. Substrates of ClpXP belong to many cellular pathways such as DNA damage response, metabolism, and transcriptional regulation. Crucially, disruption of this proteolytic complex in microbes has been shown to impact the virulence and infectivity of various human pathogenic bacteria. Loss of ClpXP impacts stress responses, biofilm formation, and virulence effector protein production, leading to decreased pathogenicity in cell and animal infection models. Here, we provide an overview of the multiple critical functions of ClpXP and its substrates that modulate bacterial virulence with examples from several important human pathogens.